2010
DOI: 10.1097/ccm.0b013e3181b788ab
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase is a novel biomarker in humans for severe traumatic brain injury*

Abstract: Objective Ubiquitin C-terminal hydrolase (UCH-L1), also called neuronal-specific protein gene product (PGP 9.3), is highly abundant in neurons. To assess the reliability of UCH-L1 as a potential biomarker for traumatic brain injury (TBI) this study compared cerebrospinal fluid (CSF) levels of UCH-L1 from adult patients with severe TBI to uninjured controls; and examined the relationship between levels with severity of injury, complications and functional outcome. Design This study was designed as prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(169 citation statements)
references
References 57 publications
(49 reference statements)
2
156
1
5
Order By: Relevance
“…141 The neuron-specific protein UCH-L1 (ubiquitin carboxyl-terminal hydrolase isozyme L1) was first linked to neurodegenerative pathology through its involvement in PD, 142 and its presence in serum was later identified as a biomarker for severe TBI. [143][144][145] Serum levels of UCH-L1 may have diagnostic utility in concussion, 146 but recent evidence suggests a lack of correlation between elevated serum levels and subconcussive hits. 147 The clinical utility of UCH-L1 in paediatric populations warrants further study.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…141 The neuron-specific protein UCH-L1 (ubiquitin carboxyl-terminal hydrolase isozyme L1) was first linked to neurodegenerative pathology through its involvement in PD, 142 and its presence in serum was later identified as a biomarker for severe TBI. [143][144][145] Serum levels of UCH-L1 may have diagnostic utility in concussion, 146 but recent evidence suggests a lack of correlation between elevated serum levels and subconcussive hits. 147 The clinical utility of UCH-L1 in paediatric populations warrants further study.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…To test this possibility, Papa et al 39 carried out a prospective study to determine the CSF levels of ubiquitin C-terminal hydrolase in patients who had severe brain injury and in uninjured controls. They found that ubiquitin C-terminal hydrolase levels were significantly increased in the CSF of brain-injured patients, and that the magnitude of this increase correlated with mortality, post-injury complications, and outcome tested 6 months post-discharge.…”
Section: Ubiquitin C-terminal Hydrolasementioning
confidence: 99%
“…Using a systems biologybased approach to select top down candidate markers, ubiquitin C-terminal hydrolase L1 (UCH-L1) has been demonstrated in both CSF and serum of both animals and humans after TBI. 135,[144][145][146][147][148][149][150][151][152] This biomarker is associated with the occurrence of neuronal cell death, particularly in association with large contusional lesions. Likewise, glial fibrillary acidic protein (GFAP) and its breakdown products may be important companion biomarkers for distinguishing focal and diffuse pathologies in TBI.…”
Section: Biomarkersmentioning
confidence: 99%